Popular co-occurrence of thyroid autoimmune disorders and specific gastrointestinal tract diseases - Ewa Tywanek; Magdalena Woźniak; Agnieszka Zwolak; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Introduction: Thyroid gland, despite of its small average size, is a crucial organ of human body. Hormones produced by the thyroid i.e. thyroxine (T4) and triiodothyronine (T3) are necessary for proper functioning the whole organism. Excess or deficiency of these hormones manifest as multiple symptoms of different organs or systems. In this review we focused on special complaints of gastrointestinal tract. Worth to notice is that some thyroid disorders are present in particular gastrointestinal disorders more frequently. Purpose: The aim of this review is to indicate co-occurrence disorders of the thyroid gland, especially autoimmune thyroiditis with disorders of some organs of gastrointestinal tract. State of knowledge: By this time we can enumerate series of thyroid diseases, i.e. hypothyroidism, hyperthyroidism, thyroid nodular goiter, neoplasms or multiple forms of thyroiditis. Generally chronic autoimmune thyroiditis is the most frequent disorders of the gland. That's the reason why we focused on coexisting this state with gastritis, chronic inflammatory bowel diseases, steatosis of the liver or with neoplasms of gastrointestinal tract. We aim to prove the necessary of constitute diagnosis towards other autoimmune diseases, when the one has bed diagnosed. Thyroid disorders may result in abnormalities of functioning particular organs of the human body. This fact may have an impact on blood tests results - for example elevation of transaminases evaluating function of the liver is often noted in thyroid diseases, what should sensitize clinicians towards performing diagnostics of thyroid function during treatment of liver or intestines or stomach dysfunction. Summary: Diseases of the thyroid gland may coexist with particular diseases of gastrointestinal tract. They may alter the course of these disorders and constitute unfavorable factor of the treatment.